'Name and shame' – director attendance disclosure and practice. Issue 2 (3rd July 2018) - Chapple, Larelle (Ellie); Gray, Stephen; Nowland, John; Sadiq, Kerrie
ABSTRACT: Three major director characteristics have been associated with board performance – independence, gender/gender diversity mix and multiple directorships. This study investigates the attendance practices of directors as a fourth director characteristic associated with director and board performance. It does so by investigating director attendance of listed companies where there is a full meeting attendance 'roll-call' disclosure regime, relative to a 'brightline' disclosure of attendance below 75%. Attendance data from Australia and the US are compared over the period 2001–2015. A comparison shows that Australian directors, on average, are 6 times more likely to attend fewer than 75% of their required board and committee meetings. This study provides previously undocumented analysis on the attendance practices of directors. The results have implications for the reporting framework of director attendance and suggest that in line with current regulatory thinking, a brightline approach has several policy advantages over a roll-call approach.